Dorsal Striatum Dopamine Levels Fluctuate Across the Sleep–Wake Cycle and Respond to Salient Stimuli in Mice - Dong, Hui; Wang, Juan; Yang, Yan-Fei; Shen, Yan; Qu, Wei-Min; Huang, Zhi-Li (Frontiers in Neuroscience, 2019)
Dopamine is involved in numerous neurological processes, and its deficiency has been implicated in Parkinson’s disease, whose patients suffer from severe sleep disorders. Destruction of nigrostriatal dopaminergic neurons or dorsal striatum disrupts the sleep-wake cycle. However, whether striatal dopamine levels correlate with vigilance states still remains to be elucidated. Here, we employed an intensity-based genetically encoded dopamine indicator, dLight1.1, to track striatal dopamine levels across the spontaneous sleep-wake cycle and the dopaminergic response to external stimuli. We found that the striatal dLight1.1 signal was at its highest during wakefulness, lower during non-rapid eye movement (non-REM or NREM) sleep, and lowest during REM sleep. Moreover, the striatal dLight1.1 signal increased significantly during NREM sleep-to-wake transitions, while it decreased during wake-to-NREM sleep transitions. Furthermore, different external stimuli, such as sudden door-opening of the home cage or cage-change to a new environment, caused striatal dopamine release, whereas an unexpected auditory tone did not. Finally, despite both modafinil and caffeine being wake-promoting agents that increased wakefulness, modafinil increased striatal dopamine levels while caffeine did not. Taken together, our findings demonstrated that striatal dopamine levels correlated with the spontaneous sleep-wake cycle and responded to specific external stimuli as well as the stimulant modafinil.